Structural Challenges, Police Reform Proposals and Protection of Lives and Property in Nigeria: Insights from SARS - Osah, Goodnews; Akpuh, Charles C. (NIU Journal of Humanities; Vol 6 No 3 (2021): KIU Journal of Humanities, Vol. 6 No. 3, September 2021, 2021)
This paper was based on the analysis of the inability of the national police to fulfil its mandate of protection of lives and property within the domestic environment of Nigeria.  From the standpoint of the dire level of insecurity in Nigeria, the paper sought to highlight, critically, some basic reasons why police reforms have often failed to produce the expected results in Nigeria, taking clues from the activities of the defunct Special Anti-robbery Squad, SARS.  The paper adopted a mono-method, qualitative, desk-research approach, which depended on secondary sources of data, structured survey, and interpretive analysis of historical facts relating to the functions of Nigeria Police.  It was discovered, among other things, that the poor performance of Nigeria Police is more of an orientational, than structural, problem.  It was concluded, therefore, that the right change in the orientation and approach of the police, the government, and other stakeholders to police reforms will make the police function expectedly.  So, it was recommended that the process of change of orientation, approach, and, maybe, structure of the police should be designed to be a collective effort of all the stakeholders. Keywords: Police Reform, Police Reform Proposal, Protection of Lives and Property, Special Anti-Robbery Squad (SARS), Structural Challenges.